Influence of environmental fctors - Temperature and precipitations - Upon the tomatoes crops - Ancuţa Marin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The diversified way of consumption of tomatoes and versatility of the species that can be grown with good results in different environmental conditions and climate have determined a particular interest for the vegetable producers. Current conceptions about balanced nutrition, grant tomato consumption a priority position, primarily because tomatoes ensures to human body a wide range of vitamins, minerals and water, so necessary for normal physiological activity of the human body. In the present paper I will present a comparative analysis of the temperature and precipitations in the period 2009-2015, during the growing period (March-September) for field tomato crops, and their influence on production. The purpose of the paper is to make some recommendations that could be useful to our vegetable growers who choose to cultivate tomatoes in field.
Keywords: 330; culture; temperatures; precipitation; production; tomatoes